Wild Hundreds - Marshall, Nate (Pitt poetry series., 2015)
Wild Hundreds is a long love song to Chicago. The book celebrates the people, culture, and places often left out of the civic discourse and the travel guides. Wild Hundreds is a book that displays the beauty of black survival and mourns the tragedy of black death.